2005
DOI: 10.1111/j.1440-1819.2005.01440.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of milnacipran on poststroke depression on inpatient rehabilitation

Abstract: Post-stroke depression (PSD) has a negative impact on rehabilitation following stroke. No satisfactory antidepressant treatment for PSD has yet been developed. The present study examined the effect of milnacipran, a serotonin and norepinephrine reuptake inhibitor, on PSD patients. Eleven PSD patients taking milnacipran in a rehabilitation hospital were compared to age-matched, sex-matched, and severity of depression at admission-matched PSD patients hospitalized during 2001 who did not take any antidepressant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 29 publications
2
6
0
Order By: Relevance
“…Several studies have shown that both depressive mood and apathy have a negative impact on the capacity of stroke patients to recover ADL 11,20,23,25,26 . Somatic symptoms, including psychomotor retardation, weakness, and lethargy, are important features of depression 13–15 . This observation is consistent with the results of the present multiple regression analysis, in which reduced mood and apathetic state was associated with sitting balance after stroke.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Several studies have shown that both depressive mood and apathy have a negative impact on the capacity of stroke patients to recover ADL 11,20,23,25,26 . Somatic symptoms, including psychomotor retardation, weakness, and lethargy, are important features of depression 13–15 . This observation is consistent with the results of the present multiple regression analysis, in which reduced mood and apathetic state was associated with sitting balance after stroke.…”
Section: Discussionsupporting
confidence: 91%
“…11,20,23,25,26 Somatic symptoms, including psychomotor retardation, weakness, and lethargy, are important features of depression. [13][14][15] This observation is consistent with the results of the present multiple regression analysis, in which reduced mood and apathetic state was associated with sitting balance after stroke. Depressive symptoms were influenced by several factors, such as age 15 and lesion location, 12,26 while the present results also suggest that trunk control, that is, sitting balance, might be an important predictive factor.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Lastly, there are few studies on the usefulness of new dual-agents SNRIs (serotonin and norepinephrine reuptake inhibitors), as venlafaxine or milnacipran and duloxetine (Dahmen et al 1999; Yamakawa et al 2005), but methodological problems (open-label studies and with small case-series) reduce the power of these data.…”
Section: Other Studiesmentioning
confidence: 99%
“…The impact of carotid disease on HRQoL has been mainly investigated for its serious form, stroke, and not for amaurosis fugax and transient ischaemic attack (TIA). Stroke often causes impairment of physical, cognitive, emotional, behavioural and social functions, which negatively affect quality of life 3 4. In most studies HRQoL scores were lower in patients with a stroke than in the general population 3 5–7.…”
Section: Introductionmentioning
confidence: 99%